2015
DOI: 10.1016/j.molcel.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Imaging Reveals a Switch between Spurious and Functional ncRNA Transcription

Abstract: Summary Eukaryotic transcription is pervasive, and many of the resulting RNAs are non-coding. It is unknown if ubiquitous transcription is functional or simply reflects stochastic transcriptional noise. By single-molecule visualization of the dynamic interplay between coding and non-coding transcription at the GAL locus in living yeast cells, we show that antisense GAL10 ncRNA transcription can switch between functional and spurious under different conditions. During galactose induction, GAL10 sense transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
122
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 40 publications
12
122
6
Order By: Relevance
“…Thus, in a genome-wide study, antisense ncRNA transcription was found to switch off corresponding sense genes under conditions of low, but not high, expression (Xu et al 2011). Similarly, a ncRNA transcribed antisense of the GAL10 gene suppressed leaky expression of GAL10 and GAL1 in glucose-containing repressing medium but not in galactose-containing inducing medium (Lenstra et al 2015). The inhibitory effect of the MIR under conditions of both low and high Pol II transcription may be a specificity of an antisense Pol III transcription unit as opposed to an antisense Pol II ncRNA transcription unit, or the range of the EGFP assay may not cover Pol II expression levels that might be differentially affected by MIR expression.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, in a genome-wide study, antisense ncRNA transcription was found to switch off corresponding sense genes under conditions of low, but not high, expression (Xu et al 2011). Similarly, a ncRNA transcribed antisense of the GAL10 gene suppressed leaky expression of GAL10 and GAL1 in glucose-containing repressing medium but not in galactose-containing inducing medium (Lenstra et al 2015). The inhibitory effect of the MIR under conditions of both low and high Pol II transcription may be a specificity of an antisense Pol III transcription unit as opposed to an antisense Pol II ncRNA transcription unit, or the range of the EGFP assay may not cover Pol II expression levels that might be differentially affected by MIR expression.…”
Section: Discussionmentioning
confidence: 94%
“…In S. cerevisiae, sense/antisense pairing has been debated, as it was first reported that sense and antisense transcripts never coexist in the same cell (Castelnuovo et al 2013). However, recent studies confirmed that although transcribed in a bimodal fashion, sense and antisense RNAs can coexist within the same cell (Nguyen et al 2014;Lenstra et al 2015) and form dsRNA structures in vivo (Drinnenberg et al 2011;Sinturel et al 2015;Wery et al 2016). In S. pombe, the most likely explanation is that Dicer and the asXUT/ mRNA duplexes are prevented for interaction due to different subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…These "transcriptional bursts" amount to "memory" between transcripts: The synthesis of one transcript is likely to be accompanied by the synthesis of another over certain time intervals. Transcriptional bursting has now been observed in yeast (Zenklusen et al 2008;Lenstra et al 2015), slime mold (Chubb et al 2006;Muramoto et al 2010;Stevense et al 2010), fly (Garcia et al 2013), mouse , and human (Yunger et al 2010) cell lines and is a significant source of expression variation between cells. In fact, subsequent steps of gene expression such as RNA export, RNA decay, translation, etc.…”
Section: Transcriptional Burstingmentioning
confidence: 99%
“…Work from many laboratories indicates that all quantities appear to be regulated. Burst size ranges from about two RNA per burst (Lenstra et al 2015) to hundreds (Raj et al 2006), and burst frequency ranges from minutes to hours. Some genes (such as housekeeping genes in yeast) do not appear to show bursting at all, and their expression levels are well approximated by a Poisson distribution (Zenklusen et al 2008;Gandhi et al 2011).…”
Section: Transcriptional Burstingmentioning
confidence: 99%